2009
DOI: 10.2220/biomedres.30.207
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in human bladder cancer cells by green tea catechins

Abstract: Cell culture and animal studies have demonstrated strong chemopreventative effects of green tea and its associated polyphenols in multiple cancers, though the exact mechanisms of action are not well understood. This in vitro study examined the antiproliferative/pro-apoptotic potential of green tea extract (GTE), polyphenon-60 (PP-60), (−)-epicatechin gallate (ECG) and (−)-epigallocatechin-3-gallate (EGCG) in both normal and malignant human bladder cells. Cell growth (proliferation/ apoptosis) was measured in U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 23 publications
0
42
0
Order By: Relevance
“…Further studies are needed to establish the relationship between EGCG and PI3K/Akt/mTOR pathway and to determine whether mTOR mediates the effects of EGCG in treating brain, prostate, cervical and bladder cancers (Hsieh and Wu, 2009;Philips et al, 2009;Qiao et al, 2009;Das et al, 2010). However, many current clinical studies focus on using green tea extract or polyphenon E in a wide range of cancers such as breast cancer, leukemia, multiple myeloma and head and neck lesions (Table 1).…”
Section: Natural Phytochemicals As Mtor Inhibitorsmentioning
confidence: 99%
“…Further studies are needed to establish the relationship between EGCG and PI3K/Akt/mTOR pathway and to determine whether mTOR mediates the effects of EGCG in treating brain, prostate, cervical and bladder cancers (Hsieh and Wu, 2009;Philips et al, 2009;Qiao et al, 2009;Das et al, 2010). However, many current clinical studies focus on using green tea extract or polyphenon E in a wide range of cancers such as breast cancer, leukemia, multiple myeloma and head and neck lesions (Table 1).…”
Section: Natural Phytochemicals As Mtor Inhibitorsmentioning
confidence: 99%
“…Certain phytochemicals are particularly eligible for the single compound type modality inasmuch as they are pleiotropic modulators of manifold signal transduction pathways and exhibit relatively low toxicity in non-cancerous cells (Khan et al, 2008;Lee et al, 2011b). Unfortunately, the currently Food and Drug Administration (FDA)-approved chemotherapeutic phytochemicals such as paclitaxel, docetaxel, vinblastine, and vincristine have only a singular molecular target (tubulin), whereas other phytochemical candidates such as (-)-epigallocatechin gallate and delphinidin have multiple molecular targets (Ermakova et al, 2006;Li et al, 2007;He et al, 2008;Kang et al, 2008;Shim et al, 2008Shim et al, , 2010Hwang et al, 2009;Ozbay and Nahta, 2011) and in vitro cytostatic/cytotoxic potency (Bin Hafeez et al, 2008;Hsieh and Wu, 2009;Philips et al, 2009;Qiao et al, 2009;Yun et al, 2009;Cvorovic et al, 2010;Das et al, 2010) but lack an advanced clinical development trajectory and regulatory approval status.…”
Section: Introductionmentioning
confidence: 99%
“…The apoptotic process in this case is thought to involve the activation of a caspase cascade regulated by proteins from the BcL-2 family [46]. A study on human bladder cancer cells also confirmed the antiproliferative properties of epigallocatechin gallate, and polyphenon 60, epicatechin gallate, and the green tea extract were shown to have similar proapoptotic effects [44].…”
Section: Dietary Polyphenolsmentioning
confidence: 80%
“…Studies conducted on cell lines and animal models have demonstrated the strong chemoprotective properties associated with its high polyphenol content [43,44]. The link between green tea and the reduced risk of many cancers is common knowledge, and successive studies have confirmed its beneficial properties.…”
Section: Dietary Polyphenolsmentioning
confidence: 99%